Sustainable transport pricing in India - Sengupta, Ramprasad (New Delhi, 2001)
The concept of sustainability, when defined in the context of pricing of any product or service like transport, refers to the conditions which can ensure sustainable development of the concerned sector. The sustainability of the development of a sector again has three aspects: (a) financial sustainability; (b) social sustainability; and (c) environmental sustainability. Financial sustainability requires the price-cost situation for a product to be such that the total value realised through price is adequate to (a) compensate all the factors of production other than capital at the competitive normal rates, (b) provide for replacement of depreciated capital stock, and (c) generate a net surplus giving at least a normal rate of profit or interest on capital employed, while the price of the product has to be competitive to ensure a reasonable share of the market for the producer. Unless these conditions are fulfilled, the production of the concerned good or service cannot continue indefinitely nor can it grow even if the demand side condition warrants growth. Sustainability of a process of production or of its growth would thus require efficient allocation of resources. It is widely recognised that competitive market conditions would ensure such efficiency of production.
Keywords: Sustainable development